(untitled) (Teacher Education through Flexible Learning in Africa (TETFLE), 2025)
This qualitative study explored teachers’ resilience in managing diverse classes in the Kunene region of Namibia, specifically the Outjo circuit. Through interviews and questionnaires with 25 teachers from both junior primary, senior primary, and secondary phases, the research examines how resilience influences teachers’ capacity to handle classroom challenges. Findings indicate that teachers view resilience as crucial for effectively navigating diverse classroom environments, supported by factors such as cultural awareness, language support, inclusive teaching practices, and communication skills. However, they faced obstacles like absenteeism, discipline issues, low self-esteem, language barriers, and tribal tensions. Additionally, teachers reported inadequate preparation due to limited training and resources, constraining their ability to implement inclusive practices. To address these issues, teachers recommended strategies like fostering self-awareness, individualised support, and incorporating learners’ first languages into instruction. These insights inform potential policy and intervention developments aimed at strengthening teacher resilience and fostering inclusive, effective learning environments in remote areas like the Outjo circuit